Non-contributory pension programs and frailty of older adults: Evidence from Mexico - Aguila, Emma (PLoS One, 2018)
Non-contributory pension programs in the developing world seek to provide older adults with an income that may improve their health and wellbeing in old age by enabling access to health care and better nutrition. There is no previous evidence of the effects of non-contributory pensions on frailty, a comprehensive measure of health and well-being of the oldest old. We aimed to estimate the effects of non-contributory pension programs on frailty of older adults in the state of Yucatan, Mexico. We use rich panel data, including objective markers and self-reported assessments of health and well-being, for 944 adults at least 70 years of age in two communities of Yucatan, Mexico. The first wave was collected in 2008; the second wave was collected in 2010, 18 months after implementation of a monthly state pension in one community and 12 months after a federal pension paid every two months in the other. We found the state pension led to a statistically significant decrease in the severity of frailty for women, but the federal pension was associated with an increase. We found no statistically significant change in the frailty index for men in either community. Among explanations for these findings are monthly payments being more likely to be spent on health care, medicines, and more regular food expenditures, enabling women who previously lacked independent means of support to increase their longer-term health. The federal program paid every two months led to irregular patterns of food expenditure and increased ownership of durable goods but had no effects on health care utilization, subsequently leading to deterioration in longer-term health for women.